Consumer's Surplus and Welfare Change in a Simple Dynamic Model - Blackorby, Charles; Donaldson, David; Moloney, David (Review of Economic Studies, 1984)
This paper shows that the discounted sum of instantaneous equivalent or compensating variations (generalized to allow for expenditure changes) is never an exact welfare indicator for a consumer whose preferences are represented by a continuous, increasing inter-temporal utility function.